The causal mechanism of farmers’ chemical fertilizer reduction: an empirical perspective from farmland transfer-in and digital extension - Li, Xiaohong; Qiao, Shiyan; Jiang, Yanjun (Frontiers in Sustainable Food Systems, 2023)
In the context of rural revitalization, farmland transfer for the purpose of scale operation has not significantly promoted green agricultural development, and it is urgent to find ways to further promote farmland transfer-in to achieve chemical fertilizer reduction. Using the data of 1298 farmers surveyed in the 2020 China Rural Revitalization Survey, this paper incorporates digital extension into the analytical framework between farmland transfer-in and chemical fertilizer reduction, analyzing their relationship in-depth. The results showed that: (1) From the basic regression results, farmland transferin and digital extension significantly reduced farmers' chemical fertilizer application. (2) From the influence mechanism, digital extension played a negative moderating role in the effect of farmland transfer-in on chemical fertilizer application, reinforcing the chemical fertilizer reduction effect of farmland transfer-in. (3) From the heterogeneity analysis, farmland transfer-in has no significant heterogeneity in food function areas, but there is heterogeneity in different terrain and fertilizer dosage. (4) In terms of the scale of farmland transfer-in, when the area of transferred farmland was less than 100 mu, farmland transfer-in significantly reduced chemical fertilizer application; otherwise, farmland transfer-in did not achieve chemical fertilizer reduction. The above findings provide a reference for promoting moderate-scale farmland transfer and synergistic construction of farmland scale operation and digital extension.